Quranic Reflections on the Story of God's Prophet Ayyub (Peace and Blessings with it) Surah Al-Anbiya's Perspective: تأملات قرآنية في قصة نبي الله أيوب - عليه الصلاة والسلام - من خلال سورتي الأنبياء وص - Khalid Hasan Ali Hussein Jayash (Walidem Institute and Publishing (WIP), 2023)
The Quranic stories contain lessons and admonitions that are worthy of reflection and contemplation, there is nothing more beneficial for a person than pondering over the Quran. One of the most remarkable examples of patience and steadfastness in the Quran is the story of the prophet (Ayyub), peace be upon him. Indeed, patience is often mentioned in conjunction with him. This research presents Quranic reflections on the story of the prophets (Ayyub), peace be upon him, as told in surahs Al-anbiya and saad. The researcher used an inductive, deductive, and descriptive approach to extract the meanings, benefits, guidance, and faith-related concepts derived from pondering over the story of the prophet (Ayyub), peace be upon him, and its impact on the Muslim community. The study consists of an introduction, three chapters, and conclusion, and indexes. The introduction covers the importance of the topic, reasons for choosing it, research objectives, previous studies, and research methodology. The first and second chapters include reflections on the story of the prophet (Ayyub), peace be upon him, in surahs Al-anbiya and saad, respectively. This is done by explaining the Quranic verses and presenting the benefits and guidance derived from pondering them. The third chapter highlights the most important faith-related concepts derived from the story of the prophet (Ayyub,) peace be upon him and their impact on the Muslim community. Through this research, the researcher found that the most important faith-related concepts derived from this story are belief in fate and destiny, supplication, and patience. The research concludes that: Pondering over and contemplating the Quranic stories is a source of comfort for those who are afflicted, The Prophet (Ayyub), peace be upon him, was afflicted with the loss of wealth, children, and health, but he remained patient and grateful to Allah until he was cured. He is a role model for those who remain patient and steadfast in adversity. Supplication is a great means of relieving worries and difficulties, bringing peace to the heart, and facilitating matters.